Model Dakwah Bil Hal dalam Sustainabilitas Pemberdayaan Kelompok Disabilitas di Yayasan Mahanani - Yunita Ayu Ardani; Saipullah Hasan (IDARI: Jurnal Manajemen Dakwah, 2026)
This study aims to analyze the sustainability of empowering persons with disabilities through the dakwah bil hal model at the Mahanani Foundation in Semarang Regency. This research employs a descriptive qualitative method with data collection techniques consisting of observation, interviews, and documentation. The findings show that the empowerment of persons with disabilities at the Mahanani Foundation is carried out through a dakwah bil hal approach that emphasizes concrete actions and the provision of direct benefits to the community. Dakwah bil hal is implemented through sewing and embroidery training, cassava-based food processing, and sports coaching. Through these programs, persons with disabilities not only acquire technical skills, but also gain opportunities to enhance their self-confidence, productivity, and ability to live independently. The sustainability of the program is reflected in the establishment of productive business units, the marketing of products created by persons with disabilities, increased economic independence, and achievements in sports. These findings indicate that dakwah bil hal can serve as an inclusive da’wah management strategy that promotes independence, dignity, and sustainable livelihoods for persons with disabilities.